Development, optimization and in vivo characterization of domperidone-controlled release hot-melt-extruded films for buccal delivery. (3rd March 2016) - Palem, Chinna Reddy; Dudhipala, Narendar Reddy; Battu, Sunil Kumar; Repka, Michael A.; Rao Yamsani, Madhusudan
Abstract: Objective : The aim of the present investigation was the development and in vivo characterization of domperidone (DOM) hot-melt extruded (HME) controlled release films by central composite design (CCD) for buccal delivery. Methods : Concentration of PEO N750 ( X 1 ) and HPMC E5 LV ( X 2 ) as independent variables and tensile strength ( Y 1 ), percent drug release at 6 h (Q6, Y 2 ) and percent drug permeated at 6 h ( Y 3, P6 ) as responses. In total, 13 formulations were prepared and studied. HME films were evaluated for drug excipient compatibility, physico-mechanical properties, drug content, in vitro drug release, bioadhesion, swelling and erosion, ex vivo permeation. Furthermore, statistically optimized formulation was subjected for bioavailability studies in healthy human volunteers. Results : Statistically optimized formulation exhibited a tensile strength (3.86 kg/mm 2 ), 93.62 ± 2.84% of drug release and 63.36 ± 2.12% of drug permeated in 6 h. HME films demonstrated no drug excipient interaction and excellent content uniformity. Furthermore, optimized formulation exhibited elongation at break (38.6% mm 2 ), peak detachment force (1.75 N), work of adhesion (3.21 mJ), swelling index (240.4%) and erosion (8.5%). Bioavailability from the statistically optimized buccal films was 3.2 times higher than the oral dosage form ( p  < 0.05). The ex vivo–in vivo correlation was found to have biphasic pattern and followed type A correlation. The stability of the optimized formulation was studied and no significant changes were detected in 6 months. Conclusion : The results indicate that hot-melt extrusion is a viable technique for the preparation of DOM buccal-adhesive controlled release films with improved bioavailability by CCD.